Systemic-Lupus-Erythematosus-Related Acute Pancreatitis: A Cohort from South China. (19th June 2012) - Yang, Yanlong; Ye, Yujin; Liang, Liuqin; Wu, Tianfu; Zhan, Zhongping; Yang, Xiuyan; Xu, Hanshi
Abstract : Acute pancreatitis (AP) is a rare but life-threatening complication of SLE. The current study evaluated the clinical characteristics and risk factors for the mortality of patients with SLE-related AP in a cohort of South China. Methods . Inpatient medical records of SLE-related AP were retrospectively reviewed. Results . 27 out of 4053 SLE patients were diagnosed as SLE-related AP, with an overall prevalence of 0.67%, annual incidence of 0.56‰ and mortality of 37.04%. SLE patients with AP presented with higher SLEDAI score (21.70 ± 10.32 versus 16.17 ± 7.51, P = 0.03 ), more organ systems involvement (5.70 ± 1.56 versus 3.96 ± 1.15, P = 0.001 ), and higher mortality (37.04% versus 0, P = 0.001 ), compared to patients without AP. Severe AP (SAP) patients had a significant higher mortality rate compared to mild AP (MAP) (75% versus 21.05%, P = 0.014 ). 16 SLE-related AP patients received intensive GC treatment, 75% of them exhibited favorable prognosis. Conclusion . SLE-related AP is rare but concomitant with high mortality in South Chinese people, especially in those SAP patients. Activity of SLE, multiple-organ systems involvement may attribute to the severity and mortality of AP. Appropriate glucocorticosteroid (GC) treatment leads to better prognosis in majority of SLE patients with AP.